The Effect of Rosiglitazone on Bone Mass and Fragility Is Reversible and Can Be Attenuated With Alendronate. (18th June 2013) - Kumar, Sanjay; Hoffman, Sandra J; Samadfam, Rana; Mansell, Peter; Jolette, Jacquelin; Smith, Susan Y; Guldberg, Robert E; Fitzpatrick, Lorraine A
ABSTRACT Rosiglitazone (RSG) is an antidiabetic drug that has been associated with increased peripheral fractures, primarily in postmenopausal women. In this report, we investigated the underlying mechanisms of RSG‐associated bone loss in ovariectomized (OVX) rats and determined whether changes in bone parameters associated with RSG administration are reversible on treatment cessation or preventable by coadministration with an antiresorptive agent. Nine‐month‐old Sprague‐Dawley rats underwent OVX or sham operation. Sham‐operated rats received oral vehicle only; OVX animals were randomized to receive vehicle, RSG, alendronate (ALN), or RSG plus ALN for 12 weeks. All treatment started the day after ovariectomy. After the 12‐week treatment period, the OVX and RSG groups also underwent an 8‐week treatment‐free recovery period. Bone densitometry measurements, bone turnover markers, biomechanical testing, and histomorphometric analysis were conducted. Microcomputed tomography was also used to investigate changes in microarchitecture. RSG significantly increased deoxypyridinoline levels compared with OVX. Significant exacerbation of OVX‐induced loss of bone mass, strength, and microarchitectural deterioration was observed in RSG‐treated OVX animals compared with OVX controls. These effects were observed predominantly at sites rich in trabecular bone, with less pronounced effects in cortical bone. Coadministration of RSG and ALN prevented the bone loss associated with RSG treatment. Following cessation of RSG treatment, effects on bone mass and strength showed evidence of reversal. Thus, treatment of OVX rats with RSG results in loss of bone mass and strength, primarily at sites rich in trabecular bone, mainly due to increased bone resorption. These effects can be prevented by concomitant treatment with ALN and may be reversed following discontinuation of RSG.